Improving Teleoperation with Vibration Force Feedback and Anti-collision Methods - Casqueiro, André; Ruivo, Diogo; Moutinho, Alexandra; Martins, Jorge (Robot 2015: Second Iberian Robotics Conference, 2016)
This paper presents a two folded solution to facilitate and improve the teleoperation of unmanned vehicles in unknown scenarios. The first part of the solution regards increasing the operators perception of the vehicle surroundings by means of a new vibration feedback transmitted by a haptic controller. The second part concerns the implementation of new anti-collision methods that take into account both vehicle and environment constraints through a spatial representation of the allowed vehicle velocities. The solution was tested and validated by 28 subjects tele-operating an omnidirectional ground vehicle through an unseen maze. The experiment results show a reduction of the human operator workload and of the time taken to complete the task. The vibration feedback was compared by the subjects with other haptic feedbacks in an experiment to identify the direction of a single obstacle, outperforming these in the effective indication of the presence and direction of the existing obstacle.